Danish Diplomacy and the Dedication of Giardino novo II (1606) to King James I - Lewis, Susan G. (Danish Yearbook of Musicology, 2001)
This article explores the use of the music book dedication as a cultural tool to advance political goals. Focusing on Melchior Borchgrevinck’s dedication of the madrigal anthology Giardino novo […] il secondo libro (Copenhagen: Waldkirch, 1606) to King James I of England, I suggest that the text forms part of a larger political and artistic programme aimed at strengthening Denmark’s ties with England. Acting on Christian IV’s behalf, Borchgrevinck extols the virtues of James I and encourages close relations between the royal houses of Denmark and England. These interests are furthered by the use of French as the dedicatory language to transmit these messages of kinship and harmony.